DEKOMPOSER ALAMI BERBAHAN LIMBAH SAYUR DENGAN PENAMBAHAN WHEY KEJU SEBAGAI SUMBER PROTEIN - anita; Rizky Meidiana Faradila; Muhammad Rio Hendratama; Nanik Astuti Rahman (Teknik Kimia ITN Malang, 2022)
Uncontrolled accumulation of vegetable waste can have a negative impact that will affect various aspects of life, either directly or indirectly. Many studies have used vegetable waste as a raw material for making fertilizers by adding EM4 as a source of decomposing microorganisms. EM4 as a source of microorganisms can be replaced with local microorganisms from a mixture of cabbage waste, cheese whey, molasses, rice bran, and coconut water. For this reason, this study uses vegetable waste, namely cabbage with variations in fermentation time and the ratio of cabbage waste and whey cheese as a natural decomposer from a mixture of vegetable waste and cheese whey which is processed by fermentation so that it can be used as a source of microorganisms in the manufacture of liquid organic fertilizer (POC). This study aims to study the effect of fermentation time and the effect of the ratio on the process of making natural decomposers from cabbage vegetable waste and cheese whey. This study uses a ratio of 30:70; 20:80; 10:90; 0:100 on a mixture of cheese whey and cabbage vegetable waste (WLs) with fermentation times of 7, 14, and 21 days. From the analysis of nitrogen levels, the highest yield was found at a ratio of WLs 20:80 of 1.54 with a fermentation time of 14 days, while analysis of phosphorus levels obtained the highest results with a ratio of WLs 10:90 of 0.77 at a fermentation time of 21 days. potassium obtained the highest yield with a ratio of WLs 30:70 of 0.41 at 21 days of fermentation. While the results of identification and analysis of the number of microorganisms showed that the manufacture of a natural decomposer solution with a fermentation time of 7 days contained 1 type of isolated lactic acid bacteria, namely Bacillus subtilis, and there were no pathogenic bacteria such as E. coli and salmonella. WL variable. 20:80, which is 15 × 104 colonies/100 mL.